Genes for Yield Stability in Tomatoes. Issue 4 (9th December 2021) - Fisher, Josef; Zamir, Dani
Abstract: Breeding plant varieties with adaptation to unstable environments requires some knowledge about the genetic control of yield stability. To further this goal, a meta‐analysis of 12 years of field harvest data of 76 Solanum pennellii introgression lines (ILs) is conducted. Five quantitative trait loci (QTL) affecting yield stability are mapped; IL10‐2‐2 is unique as this introgression improved yield stability without affecting mean yield both in the historic data and in four years of field validations. Another dimension of the stability question is which genes when perturbed affect yield stability. For this the authors tested in the field 48 morphological mutants and found one 'canalization' mutant ( canal‐1 ) with a consistent effect of reducing the stability of a bouquet of traits including leaf variegation, plant size and yield. canal‐1 mapped to a DNAJ chaperone gene (Solyc01g108200) whose homologues in C. elegans regulate phenotypic canalization. Additional alleles of canal‐1 are generated using CRISPR/CAS9 and the resulting seedlings have uniform variegation suggesting that only specific changes in canal‐1 can lead to unstable variegation and yield instability. The identification of IL10‐2‐2 demonstrates the value of historical phenotypic data for discovering genes for stability. It is also shown that a green‐fruited wild species is a source of QTL to improve tomato yield stability. Abstract : Breeding tomatoes for stable yield. Using 12 years of field data, five quantitative trait loci that affect the variation in fruit yield are found in introgression lines from wild tomato. One QTL stabilizes yield without affecting mean yield. In contrast, a screen for morphological mutants in production tomato lines found one locus that reduces stability in fruit yield, leaf variegation, and plant size.